2005
DOI: 10.1007/s00404-005-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Water birth: is the water an additional reservoir for group B streptococcus?

Abstract: Regarding GBS colonization of the newborn during water birth there might be a wash out effect, which protects the children during the delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
3
8
0
3
Order By: Relevance
“…A small study showed that after water birth the bath water was significantly more often colonized with GBS (13/20; 65%) than after immersion followed by a delivery in bed (4/16; 25%), (P = 0.022) [14], supporting our hypothesis that GBS can be transmitted through immersion water.…”
Section: Discussionsupporting
confidence: 75%
“…A small study showed that after water birth the bath water was significantly more often colonized with GBS (13/20; 65%) than after immersion followed by a delivery in bed (4/16; 25%), (P = 0.022) [14], supporting our hypothesis that GBS can be transmitted through immersion water.…”
Section: Discussionsupporting
confidence: 75%
“…39 Newborn microbial colonization was measured in 3 studies. 31,46,47 Zanetti-Dallenbach et al initially reported no difference in group B streptococcus (GBS) colonization among neonates born in water or conventionally, but their subsequent study revealed a lower GBS colonization rate among neonates born underwater, 46 leading to speculation that there may be a "wash-out effect" associated with waterbirth. 47 Fehervary et al examined the general colonization of neonates born underwater compared with neonates after water labor and neonates whose mothers labored and birthed without immersion.…”
Section: Infection and Antibiotic Administrationmentioning
confidence: 99%
“…In addition, Geissbuehler et al 10 and Thoeni et al 11 found that waterbirth decreases the number of episiotomies and perineal lacerations. In relation to neonatal outcomes, one study showed a significant increase in neonatal arterial blood pH and an increased Apgar score 10 ; however, three other studies showed no differences in either 9,11,13 …”
Section: Introductionmentioning
confidence: 98%